Strategi Marketing Communication Mix: Studi Kasus Wisata Alam pada Desa Minggirsari Kabupaten Blitar - Wijayanti, Anita Reta Kusuma; Sari, Hesty Puspita (Institut Teknologi Sepuluh Nopember, 2023)
Following the pandemic, there has been a surge in interest in natural tourism as a means to attract travelers. Minggirsari Village, since 2019, has been actively harnessing its natural resources to entice tourists and has emerged as a trailblazing model village in Blitar Regency, successfully preserving and leveraging its natural splendors for tourism. This study endeavors to delineate Minggirsari's marketing communication strategy in promoting its natural destinations, employing the Marketing Communication Mix model. The qualitative case study methodology was employed, involving on-site observations, interviews with tourism managers, and activity documentation to gather and subsequently analyze data, following the Miles and Hubbermen theory's stages of data collection, processing, presentation, and conclusion drawing. Minggirsari Village's Nature Tourism employs a diverse marketing communications mix encompassing personal sales, advertising, promotions, and public relations to augment tourist footfall, encapsulated by the rallying cry